Parameter Optimization of Segmental Multicluster Fractured Horizontal Wells in Extremely Rich Gas Condensate Shale Reservoirs - Zhipeng, Wei; Jinwei, Wang; Rumin, Liu; Tao, Wang; Guannan, Han (Frontiers in Earth Science, 2021)
For economic and efficient development of extremely high condensate shale gas reservoirs, an dual-medium numerical model of segmental multi-cluster fractured horizontal well was established considering the effect of condensate and desorption, and the optimization of fracturing segments, fracturing clusters, half-length of main fracture, fracture permeability, fracture mesh mesh density and fracture laying distribution patterns were studied. It is The results show thatindicated that the horizontal well whose design length is 2700m has performsthe best development effect when it has 43 fracturing segments with 3 clusters in a each segment and the fracture permeability is 300mD. The production capacity of horizontal wells is positively linearly correlated with the half-length of fractures. Increasing fracture half-length is would be an effective way to tap potential ofproduce condensate oil near wellbore. An effective fracturing fractured reconstruction area can be formed,constructed to remarkably improve productivity and the effect of increasing production is remarkable when the half-length of the fracture is 50m and the number of secondary fractures reaches is 4 in the singleeach segment. On the basis of reasonable fracture parameters, the staggered type interlaced distribution pattern is beneficial to the efficient development of shale gas-condensate reservoirs because of its large reconstruction volume, far pressure wave, small fracture interference and small precipitation range of condensate. The research content of this paper gives some guiding significance for the parameter optimization of segmental fractured horizontal wells in the same kind of gas reservoirs.